Advances in applying somatosensory interaction technology in geriatric care: A bibliometric analysis - Changle Pei; Weibo Lyu; Jingxia Liu; Yan Wang; Wenjia Ye; Zhou Zhou; Kangyao Cheng (International Journal of Nursing Sciences)
Objectives: Somatosensory Interaction Technology (SIT) is used in various aspects of geriatric care. We aimed to conduct a bibliometric analysis to summarize relevant publications and visualize publication characteristics, current hotspots, and development trends, thereby inspiring subsequent researches. Methods: We searched the Web of Science Core Collection database for publications on the application of SIT in geriatric care. Bibliometric visualization and clustering analysis were performed using VOSviewer V1.6.18 Software, while keywords burst detection analysis was conducted with CiteSpace 6.1.R6 Software. Results: After screening, a total of 1,019 publications were included. The number of publications on SIT in geriatric care is gradually increasing, exhibiting a rapid growth rate. The United States, Canada, and Australia led in terms of publication volume. Keyword clustering analysis identified major research hotspots: crisis warning, somatic abilities, rehabilitation training and psychosocial support. Initial studies primarily explored themes such as recovery, movement, systems, and later shifted towards gait analysis, muscle strength, parameters, and home-based care. More recently, research themes have evolved to dementia, machine learning, and gamification. Conclusions: SIT is innovative for promoting active aging, advancing intelligent healthcare, and elevating the daily quality of life for older adults in clinical and domestic settings. Applications of SIT can be categorized into early warning systems for crises, detailed analyses of physical conditions, rehabilitation enhancement, and support for psychosocial health. Research trends have transitioned from whole-body recognition to precise feedback, from a focus on physical health to mental health, and from technical feasibility to user-friendliness. Future research should focus on developing accessible and user-friendly devices, fostering interdisciplinary collaborations for innovation, expanding research to address both the physical and mental health needs of diverse older adults, and integrating emerging technologies to enhance data precision and accelerate the development of intelligent platforms.